TRANSFORMASI DIGITAL PERGURUAN TINGGI MENGGUNAKAN PRINSIP SMART EDUCATION - Dedy Ardiansyah (LPPM STMIK El Rahma Yogyakarta, 2022)
The digital world is marked by changes in the economy, companies and society become completely digital. Economic activities that are supported by the internet, products become digital, and community activities that always use the internet, make universities must prepare themselves to face these changes. SMART Education is an aspect that is used as a measure of digital transformation. The SMART principle consists of 2 two components. The first component consists of: self-directed/independence, Motivated/motivated, Adaptive/adaptation, Research/research and innovation, Technology/technology. The second component is the structural area of ​​higher education which consists of: management systems, human resources, educational activities, research and innovation, as well as higher education infrastructure. The stages of digital transformation towards SMART University are measured based on the combination of the components of SMART education principles and the components of the structural area of ​​higher education, which are categorized into three stages, namely the informatization, integration and digitization stages.